The Influence of Intellectual Capital to Market Value with Return on Assets as Intervening Variable - Marcellina Yovita; Gia Kardina Prima Amrania (Journal of Accounting Auditing and Business, 2018)
This research using leverage as the control variable to measure the relationship between IC and ROA and IC – market value indirect relationship. IC was measured with VAICTM method; ROA was used as the measurement that represented profitability. The market value was measured with a price-to-book value (PBV) ratio. The research was conducted on 215 companies in Indonesia Stock Exchange as samples in 2014 from six industry sectors those included in high-IC intensive classification by GICS. Analysis descriptive method was used on secondary data. MS Excel and EViews were used to process the data. F-test and t-test were used to test the hypothesis on 5%-significance. The results showed that IC influences ROA significantly; simultaneously and partially. IC also influences market value directly and indirectly through ROA, though the indirect influence is greater.